REFLECTIVE TEACHING PRACTICE OF PRE-SERVICE TEACHERS FOR YOUNG LEARNERS AT A TEACHER TRAINING INSTITUTE - Mustaqima, Dini (2013)
The research reported was focused on revealing the learning evidence of pre-service teachers (PRESETs) by working on reflective teaching (RT) practice in teaching English to young learners (TEYL). Narrative inquiry as a part of qualitative research design was employed for this research, and the data were obtained through the analysis of 35 reflective journals of PRESETs Year 2009. The data were then subjected to the thematic coding, categorization, and clusters by Constant Comparative Analysis method (Hewitt-Taylor, 2001). The findings revealed the evidence of PRESETs' learning through RT practice which include the knowledge of teaching aspects, the instructional skills, as well as the teaching knowledge and skills needed for improvement. Based on the findings, it is expected that the research could inspire teachers in doing reflection as well as teacher training institute to improve the teaching practice quality of their PRESETs in TEYL field by the practice of reflective teaching. Keywords: professional development, reflective teaching, pre-service teacher, teaching English to young learners